PENGARUH PENGEMBANGAN POLA PIKIR MASYARAKAT SEBAGAI UPAYA OPTIMALISASI PEMANFAATAN POTENSI LOKAL UNTUK MENINGKATKAN EKONOMI PADA USAHA KECIL DI DESA GAMBIRAN KECAMATAN PAMOTAN - Nurhidayati, Anik; Rikah, Rikah (JAB (Jurnal Akuntansi & Bisnis), 2020)
The Influence of Community Mindset Development as an Effort to Optimize the Utilization of Local Potential to Improve the Economy of Small Businesses in Gambiran Village, Pamotan District, while the expected objectives in this study are to analyze and dissect the allocation of economic resources through local potential with local potential in the rural area of Gambiran Village, Rembang Regency. Development that involves local resources and can be enjoyed by local communities is a measure of the success of a locally based economy. The increasing local-based economy does not make local residents merely spectators and observers outside the system, but involves them in the development of the economy itself. This local potential will open up local people's access to technology, markets, knowledge, capital, better management, as well as wider business relationships. Local potential in rural communities is very interesting to study where the majority of business managers are housewives whose knowledge and abilities are limited but can also contribute to the family's economic growth.Â Keywords: gender integration, local potential, economic improvement